Factors affecting students’ choice of educational administration major: Why do students join the program? - Didik Wardaya; Lantip Diat Prasojo; Sugiyono Sugiyono (Institute of Advanced Engineering and Science, 2021)
The study examined factors affecting Behavioral Intention (BI) regarding students’ choice of educational administration as their major. Samples were taken from Indonesian students. The process was begun with the adaptation of survey instruments from previous studies validated through content validity. In testing the normality, Skewness and Kurtosis values were computed. Reliability assessment was applied through Cronbach’s alpha. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were both conducted for the constructs. In examining the relationship, Structural Equation Modeling (SEM) analysis using AMOS 23.0 was applied to 257 responses. The findings informed that two relationships were significant while the other two are insignificant. Perceived Behavioral Control (PBC) and Attitude (AT) significantly predicted BI, while Subjective Norm (SN) and Facilitating Condition (FC) did not significantly predict BI. The current study can expand an in-depth contribution and reference for further researchers as a basis of the empirical evidence in relation to the validated survey questionnaire. Access to the questionnaire may contribute to educational stakeholders establishing policies to improve students’ interests in studying in an educational administration study program.